EFFECTIVE USE OF INNOVATIONS IN THE DEVELOPMENT OF PILGRIMAGE TOURISM IN UZBEKISTAN (World Bulletin of Management and Law, 2023)
The scientific article contains proposals and recommendations for the development of ziyarah tourism in the country and the organization of services to visitors at the level of international standards and the effective use of innovations